Financially Smart, Strategically Great: Managerial Financial Literacy as the Key to Growth - Yatimin Yatimin; Adi Musharianto (Maneggio, 2025)
Financial literacy in the managerial context is no longer merely an additional skill, but has evolved into one of the key foundations that are critically important for the sustainability and advancement of an organization. In facing the complex challenges posed by global economic uncertainty and the rapidly accelerating wave of digital transformation, the ability to understand and apply financial principles strategically becomes the key to maintaining organizational sustainability and competitiveness. This article thoroughly examines the importance of managerial financial literacy as a core competency that not only supports data-driven decision-making processes but also contributes to improving the efficiency of organizational resource management. Through a qualitative research method with a descriptive approach, data were collected via semi-structured interviews with managerial actors and relevant document analysis to gain a comprehensive understanding of financial literacy practices within organizational environments. Findings from this study show that when strong financial understanding is combined with the use of modern financial technologies, the result is a significant improvement in various managerial aspects. This includes enhanced capability in maintaining cash flow stability, more effective investment planning, and increased operational efficiency that supports the organization's competitive advantage. Therefore, the main conclusion of this study emphasizes that managerial financial literacy, when synergistically combined with digital skills and practical experience in organizational management, constitutes a highly valuable strategic asset. This asset deserves to be an integral part of comprehensive organizational development policies, including in human resource planning and future leadership capacity-building strategies.